The influence of hydrogen saturation on the wear mechanism of steel - Shchepetov, V.V.; Bys, S.S.; Byalik, M.R.; Medvedchuk, V.Yu.; Bys, Ya.S. (Problems of Tribology, 2025)
The tribological characteristics of hydrogenated steel 60C2 with different structural states were compared with the obtained results of studies of friction surfaces by physicochemical methods, which allowed us to draw a conclusion about the relationship between friction and wear indicators with the processes occurring on the surface of the material during friction, and the significant influence of hydrogen present in the contact zone on them. It was proven that during friction on the contact surface of hydrogenated steel 60C2, regardless of its structural state, the process of formation of secondary structures occurs, which determine the process of friction and wear of the material. Reduction of the wear intensity of steel 60C2 with a tempered martensite structure (300°C) is accompanied by the formation of secondary structures on the surface, which have a higher resistance and shield the base material from direct contact and destruction. In addition, the saturation of the material with hydrogen changes the nature and mechanism of formation of secondary structures, which in turn leads to a change in the mechanism of friction and wear of the material.